Rare and Unusual Raptors of Northern Belize - Venetia Briggs-Gonzalez; Elizabeth Scarlett; Justin Dalaba; Frank J Mazzotti (EDIS)
The second smallest country in Central America, Belize has a stunning array of natural areas that is only matched by the remarkable diversity of animals that call them home. A small human population and strong conservation ethics have preserved nearly 75 percent of Belize in its natural state. This guide lists some of the rarer and more unusual raptors you might encounter while birding in northern Belize.